Feasibility for the installation of a cocoa liquor processing industry - Muñoz Murillo, José Patricio (2019)
In the feasibility study for the installation of a cocoa liquor processing industry, it was determined through a market study that there is an 89% demand for the product with a production capacity of 19,608 liters per year; an investment of $ 77,344.42 is required for the implementation and start-up of the project that will have a useful life of 10 years, the net present value is of 4,847.48 and the internal rate of return in a 7.20%